REGIONAL INVESTMENT FINANCIAL REPORT ANALYSIS IN BADUNG REGENCY - I Nyoman Tingkes; Ida Ayu Putu Sri Widnyani (DIA: Jurnal Administrasi Publik, 2021)
The purpose of this study was to analyze the effect of financial reports through symmetric information on increasing investment in Badung Regency, Bali Province. This study was designed using quantitative research methods on data sourced from reports on budget realization and income, reports on changes in excess budget balances, balance sheets, operational reports, reports on changes in equity, cash flow reports, and notes to financial statements from 2016 to 2020. The results of the study found that the liquidity ratio is 6.09, the solvency ratio is 0.017, the activity ratio is 27.83, the profitability ratio consists of ROI-6.77 and ROE-0.22, and the ratio of direct spending to indirect spending is 0.88. Specifically, for the investment in capital-output ratio-ICOR, it was found that the average economic growth per year was 5.29 percent. Based on the results of this study, it can be suggested to the Badung Regency Government that (a) the collection of tax and levy receivables be more optimized, (b) there needs to be a policy regarding the budget deficit, (c) increase direct spending at least equal to or more than the apparatus expenditure, and (d) further improve operating cost efficiency. In addition, spending on grants and social assistance should be more directed at spending on goods and services that are truly vital and strategic.